Women’s social movements and the classification of feminism in Iran - Vakhshiteh, A. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2022)
This article is devoted to the analysis of the development of women’s social movements in the Islamic Republic of Iran. When we talk about the women’s movement, we are talking about several identities, each of which has its own manifestation. In addition, all women and even men who, in one way or another, consider themselves participants in the women’s movement and adhere to different feminist approaches, have many other identities. The Iranian women’s movement is not exception to this principle and has been formed since the Qajar dynasty (1725-1996). During the Pahlavi era (1925-1978), the women’s movement developed within the framework of the state approach, and after the Islamic Revolution in Iran during the Islamic Republic of Iran (from 1978 to the present), “secular feminism” developed along with Islamic identity and “Islamic feminism”. Iranian society has traditionally been a male (patriarchal) society, and under the influence of religion, patriarchy has grown significantly. Therefore, the women’s social movement in Iran emerged as a movement for equal rights for men and women, primarily for the right to education and the right to vote. The second stage in the development of the women’s movement also focuses on women’s rights and women’s emancipation and actualizes such issues as the right to divorce and opposition to the forced wearing of the hijab (veil), as well as other issues related to the dignity of a woman as a free person. At the same time, a distinctive feature of the development of women’s social movements in Iran was that along with the social dimension of this phenomenon, a political one also emerged, since the Iranian government at different stages opposed the Feminist agenda.